CRITICAL THINKING IS AN IMPORTANT SKILL FOR EVERY STUDENT - Farida Azamovna Pulatova (Scholar Express Journals, 2023)
Critical thinking requires getting to know different, sometimes conflicting, opinions about a problem. Interest for knowledge are the basis of critical thinking, and to satisfy this desire, it is necessary to formulate questions in a correct way. A sufficient amount of knowledge is necessary to think critically about the world around us. The more knowledge you have, the easier it is to compare and analyze. Before making a critical assessment of the problem, it is necessary to consider it from all sides, to see the situation in the context of other events, to monitor its development in time.
Keywords: students; time; critical thinking